EVALUATION OF PASSENGER SERVICES AT THE PORTFASTBOAT SAMPALAN OF BALI PROVINCE USING CUSTOMER SATISFACTION INDEX (CSI) AND IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHOD - Wibisono, Yohan; Setiawan, Bambang; Firzatullah, Raden Muhamad; Taufiqurrahman, Muhammad; Manurung, Wim Benhard; Lestari, Lestari (IWJ : Inland Waterways Journal, 2025)
Sampalan Ferry Port serves the Sampalan-Sanur and Sampalan-Kusamba routes. From the results of a field survey based on the regulation of the Director General of Land Transportation Number KP-DRJD 6188 of 2024 concerning Guidelines for Assessment and Supervision of the Implementation of Ferry Port Service Standards, it was found that several services for service users had not been implemented properly, such as temperature control facilities, parking area instructions, CCTV that could not see the entire vehicle parking area, gangways and evacuation assembly points. As well as the unavailability of zoning signs A1, A2, A3, evacuation route instructions, information on further transportation, first aid kits, health clinics/posts and breastfeeding rooms. This study used the Customer Satisfaction Index (CSI) method to determine the index of service user satisfaction with passenger services, and the mapping of the Importance Performance Analysis (IPA) quadrant to determine the priority scale of service attributes according to the interests of service users. Based on the analysis using the CSI method, the service user satisfaction index was 70.38%, and this criterion was categorized as satisfied. Based on the IPA quadrant mapping analysis, the attribute in quadrant I, which is the top priority for improvement, is the temperature control facility in the terminal building.